QRIS Efficiency in Improving Digital Payment Transaction Services for Culinary Micro-Small and Medium Enterprises in Depok City - Listiawati, Rodiana; Vidyasari, Rahmanita; Novitasari, Novitasari (Indonesian Operations Research Association (IORA), 2022)
Currently, one of the most popular electronic payment methods is using QR (Quick Response) code. As the first step transformation in Indonesian Payment System to help accelerate the development of the digital economy and finance, Bank Indonesia has issued QRIS (Quick Response Code Indonesian Standard) as unification of various QR type from various e-wallet that use QR codes. The unification of QR codes is certainly a good breakthrough, but there is fee MDR (Merchant Discount Rate) that is charged to the MSMEs (Micro-Small and Medium Enterprises) if they are using QRIS, that makes problem for them. The main purpose of this research is to analyze the efficiency of QRIS in helping to add payment service to customers in digital payment transaction for MSME. The research method used is a quantitative method by distributing questionnaires to 114 culinary MSMEs in Depok city. The result show that using QRIS makes digital payment for culinary MSMEs in Depok more efficient.